2002
DOI: 10.1039/b200633m
|View full text |Cite
|
Sign up to set email alerts
|

Toxic equivalency factors for PAH and their applicability in shellfish pollution monitoring studies©British Crown copyright 2002.

Abstract: Fish and shellfish are exposed to a wide range of polycyclic aromatic hydrocarbons (PAH) following oil spills at sea, and can become contaminated as a result. Finfish have a more effective mixed-function oxidase enzyme system than shellfish, and are therefore able to metabolise and excrete PAH more effectively than the invertebrates. Thus, contamination by high-molecular weight PAH, including those with carcinogenic potential and so of concern with regard to human consumers, is therefore usually observed in sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 18 publications
0
53
0
Order By: Relevance
“…The concentration of each of the individual PAH compounds is multiplied by its TEF proposed by (Nisbet and LaGoy, 1992) (Table 1), and these values are summed to yield benzo(a) pyrene equivalent concentrations, TEQBaP (AFSSA, 2003). This technique has been applied successfully to smoked and fresh seafood monitoring studies, and other wider monitoring programmes (Law et al, 2002). The mutagenicity of individual PAHs relative to B(a)P had also been computed using the mutagenic equivalency factor (MEF) proposed by Durant et al (1996Durant et al ( , 1999 as shown in Table 1.…”
Section: Benzo[a]pyrene Equivalent Estimationmentioning
confidence: 99%
“…The concentration of each of the individual PAH compounds is multiplied by its TEF proposed by (Nisbet and LaGoy, 1992) (Table 1), and these values are summed to yield benzo(a) pyrene equivalent concentrations, TEQBaP (AFSSA, 2003). This technique has been applied successfully to smoked and fresh seafood monitoring studies, and other wider monitoring programmes (Law et al, 2002). The mutagenicity of individual PAHs relative to B(a)P had also been computed using the mutagenic equivalency factor (MEF) proposed by Durant et al (1996Durant et al ( , 1999 as shown in Table 1.…”
Section: Benzo[a]pyrene Equivalent Estimationmentioning
confidence: 99%
“…TEFs were devised to compare the carcinogenic potency of the individual PAH with the carcinogenicity of benzo[a]pyrene (expressed as BaPeq), which is considered to be one of the most toxic of the PAHs and is often used as an indicator for this group of compounds. To date, only a few proposals for the TEFs for PAHs are available; a good summary of TEFs reported in literature is provided by Law et al (2002). Among them, the list of the TEFs proposed by Nisbet and LaGoy (1992) seems to better reflect the actual state of knowledge on the human health risk associated with inhalatory exposure to PAH mixtures.…”
Section: Pah Emissionsmentioning
confidence: 99%
“…Toxic equivalency factors are used to evaluate contamination (23). In the case of PAHs, the carcinogenic potency of individual PAHs is expressed relative to that of benzo[a]pyrene (BaPE).…”
Section: Discussionmentioning
confidence: 99%
“…The equivalency values of individual PAHs are summed to yield the total BaPEs. A number of sets of toxicity/potency equivalency factors can be found in the literature, as presented by Law (23), though all are based on a unit value for benzo [a]pyrene because the toxicology data for this compound are much better than the data for other PAHs (23). These various sets of factors differ in the data used in the calculation: Data are selected according to the matrices of interest, so that the factors applied for particular compounds may be different.…”
Section: Discussionmentioning
confidence: 99%